Core Strength Training, Balance to Increase Togok Flex and Leg Strength in the Elderly in Semarang - Muchammad Ichwal Akbar Maulana; Sri Sumartiningsih; Ipang Setiawan (JUARA : Jurnal Olahraga, 2023)
This study aimed to determine core strength training, balance to increase torso flexibility and leg strength in an elderly in Semarang. The research method is an experiment using a 2x2 factorial design. The sample consisted of 20 older women who were selected by purposive sampling. The results in this study are that are significant differences in the effect of (1) core strength training (floor and seated), (2) balance (high and low), (3) and there is the interaction of core strength training and balance to increase torso flexibility and leg strength an elderly